2021
DOI: 10.1111/nuf.12577
|View full text |Cite
|
Sign up to set email alerts
|

Chronic disease self‐care: A concept analysis

Abstract: The purpose of this concept analysis is to clarify and analyze the concept of self‐care. Self‐care is vital in the prevention, control, and management of chronic disease. It is substantially important in all aspects of health and all levels of care, and it is key to chronic disease management. Walker and Avant's (2011) method for concept analysis was used. A literature search was performed using the Cumulative Index to Nursing and Allied Health Literature, Psych INFO, Cochrane Library, Embase, Medline, and Goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…We read with interest the recently published article, "Chronic disease self-care: A concept analysis," authored by Tulu et al 1 We concur with the authors that the lack of clarity in the term self-care represents an important limitation for the development of research and clinical practice in this field. We have been studying self-care as it is performed by individuals with a chronic condition for more than two decades.…”
Section: Dear Editormentioning
confidence: 62%
See 2 more Smart Citations
“…We read with interest the recently published article, "Chronic disease self-care: A concept analysis," authored by Tulu et al 1 We concur with the authors that the lack of clarity in the term self-care represents an important limitation for the development of research and clinical practice in this field. We have been studying self-care as it is performed by individuals with a chronic condition for more than two decades.…”
Section: Dear Editormentioning
confidence: 62%
“…Reviewing the literature, we also found that the concept is huge and complex to synthesize. [2][3][4] However, looking at table 1 of the article by Tulu et al, 1 where definitions of self-care are "chronologically" reported, we struggled to recognize the sequence of our theoretical developments, so here we clarify it. In 2008, a situation-specific theory of self-care in people with heart failure was formalized by Riegel and Dickson.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Self care management can be defined as an activity carried out by patients with the intention of improving health or preventing disease (Tulu et al, 2021) (Godfrey et al, 2011) (Pun et al, 2009). The purpose of self-care behavior is to improve a person's welfare, due to their awareness of the time frame for sustaining life, continuing personal development and healthy functional life (Kitson et al, 2022) (Riegel et al, 2021) (Ziguras, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…, 2021 ). There are a variety of activities and areas that are considered self-care, which range from daily activities like maintaining personal hygiene and cleanliness in personal spaces to lifestyle and socialization activities such as ensuring proper nutrition and doing physical exercise and sports ( Tulu et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 99%